High availability network fundamentals - Oggerino, Chris (Cisco, 2001)
A practical guide to modeling and designing reliable networks Provides a detailed introduction to modeling availability necessary for network design Helps network designers understand the theoretical availability of their topologies Explains the factors that limit availability to minimize the number of network failures Provides all the information necessary to do basic availability modeling/budgeting High Availability Network Fundamentals discusses the need for and the mathematics of availability, then moves on to cover the issues affecting availability, including hardware, software, design strategies, human error, and environmental considerations. After setting up the range of common problems, it then delves into the details of how to design networks for fault tolerance and provides sample calculations for specific systems. Also included is a complete, end-to-end example showing availability calculations for a sample network.